Associations Between Residential Proximity to Traffic and Vascular Disease in a Cardiac Catheterization Cohort. Issue 1 (January 2018) - Ward-Caviness, Cavin K.; Kraus, William E.; Blach, Colette; Haynes, Carol S.; Dowdy, Elaine; Miranda, Marie Lynn; Devlin, Robert; Diaz-Sanchez, David; Cascio, Wayne E.; Mukerjee, Shaibal; Stallings, Casson; Smith, Luther A.; et al.
Abstract : Objective—: Exposure to mobile source emissions is nearly ubiquitous in developed nations and is associated with multiple adverse health outcomes. There is an ongoing need to understand the specificity of traffic exposure associations with vascular outcomes, particularly in individuals with cardiovascular disease. Approach and Results—: We performed a cross-sectional study using 2124 individuals residing in North Carolina, United States, who received a cardiac catheterization at the Duke University Medical Center. Traffic-related exposure was assessed via 2 metrics: (1) the distance between the primary residence and the nearest major roadway; and (2) location of the primary residence in regions defined based on local traffic patterns. We examined 4 cardiovascular disease outcomes: hypertension, peripheral arterial disease, the number of diseased coronary vessels, and recent myocardial infarction. Statistical models were adjusted for race, sex, smoking, type 2 diabetes mellitus, body mass index, hyperlipidemia, and home value. Results are expressed in terms of the odds ratio (OR). A 23% decrease in residential distance to major roadways was associated with higher prevalence of peripheral arterial disease (OR=1.29; 95% confidence interval, 1.08–1.55) and hypertension (OR=1.15; 95% confidence interval, 1.01–1.31). Associations with peripheral arterial disease were strongest in men (OR=1.42; 95% confidence interval, 1.17–1.74) while associations with hypertension were strongest in women (OR=1.21; 95% confidence interval, 0.99–1.49). Neither myocardial infarction nor the number of diseased coronary vessels were associated with traffic exposure. Conclusions—: Traffic-related exposure is associated with peripheral arterial disease and hypertension while no associations are observed for 2 coronary-specific vascular outcomes. Abstract : Supplemental Digital Content is available in the text.